Technical and Financial Parameters Effect Concession Period: A Study - Bagui, Swapan Kumar; Ghosh, Ambarish (Indian Journal of Finance, 2010)
Inadequate transport infrastructure has been recognized as an impediment to the industrial and economic progress of any country. Governments worldwide invariably must cope with the widening gap between needed investments and available budgetary resources. They increasingly attempt to involve the private sector in the financing, design, construction, and operation of major infrastructure projects, with a view to exploit the private initiatives to implement public projects. In this context, the BOT concept is becoming a popular mode of privatization of transport infrastructure development (Tiong 1990)1. In recent years, governments in many countries have begun privatizing transportation infrastructure sectors .Some of the forces driving this movement include a scarcity of public resources, an increase in the demand for better service and a political trend toward the deregulation of infrastructures from public monopoly. Although the discussion and case study relate to conditions in municipalities in India, the inferences are likely to be of interest to transport infrastructure managers in developing countries and to those interested in the globalization of BOT projects.